PENGARUH KEPEMIMPINAN, KARAKTERISTIK PEKERJAAN DAN KEMAMPUAN KERJA TERHADAP KINERJA KARYAWAN PT PETROKIMIA GRESIK - Yanti, Eli Delvi (Universitas Negeri Medan, 2022)
The purpose of this study was to analyze the influence of leadership, job characteristics and work ability on the performance of employees of PT Petrokimia Gresik Medan. The data collected in this study were primary data and secondary data, which were collected through data collection instruments in the form of questionnaires, interviews and documentation studies. The sample in this study were 45 respondents. This study uses quantitative data, with multiple linear regression method. The test results show that partially the leadership variable has a positive and significant effect on employee performance. Job characteristics variables have a positive and significant effect on employee performance. The work ability variable has a positive and significant effect on employee performance. Meanwhile, simultaneously, the variables of leadership, job characteristics and work ability have a positive and significant effect on company performance. Keywords: Employee Performance, Leadership, Job Characteristics and Workability